The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12885-022-09616-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel and sensitive DNA methylation marker for the urine-based liquid biopsies to detect bladder cancer

Abstract: Background Better prognostic outcome is closely correlated with early detection of bladder cancer. Current non-invasive urianalysis relies on simultaneously testing multiple methylation markers to achieve relatively high accuracy. Therefore, we have developed an easy-to-use, convenient, and accurate single-target urine-based DNA methylation test for the malignancy. Methods By analyzing TCGA data, 344 candidate markers with 424 primer pairs and prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…Of all epigenetic modifications, DNA methylation has become the most intensely studied epigenetic modification in mammals. The covalent addition of a methyl group occurs generally in cytosine within cytosine‐guanine dinucleotide (CpG) islands 135,136 . In particular, hypermethylation that represses transcription of associated gene promoter regions leading to gene silencing has been most extensively studied because of its critical role in human carcinogenesis 137,138 .…”
Section: Urinary Liquid Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Of all epigenetic modifications, DNA methylation has become the most intensely studied epigenetic modification in mammals. The covalent addition of a methyl group occurs generally in cytosine within cytosine‐guanine dinucleotide (CpG) islands 135,136 . In particular, hypermethylation that represses transcription of associated gene promoter regions leading to gene silencing has been most extensively studied because of its critical role in human carcinogenesis 137,138 .…”
Section: Urinary Liquid Biopsymentioning
confidence: 99%
“…The covalent addition of a methyl group occurs generally in cytosine within cytosineguanine dinucleotide (CpG) islands. 135,136 In particular, hypermethylation that represses transcription of associated gene promoter regions leading to gene silencing has been most extensively studied because of its critical role in human carcinogenesis. 137,138 Detected with the use of a polymerase chain reaction (PCR) on urinary cells, several DNA methylation genetic markers have been investigated increasingly in prostate cancer.…”
Section: Dna-based Markersmentioning
confidence: 99%
“…Multiple gene sites in BC are hypermethylated, including Reprimo (RPRM), prostaglandin-endoperoxide synthase 2 (PTGS2), glutathione stransferase pi 1 (GSTP1) and APC regulator of the Wnt signalling pathway. By performing methylation-specific RT-qPCR on 477 urine samples (137 BCs, 202 control samples, 28 benign BCs and other related urinary cancer samples), Deng et al 60 found that the methylation level of DMRTA2 shows higher sensitivity in detecting early stages of BC (94.1% for T1, 96.4% for T2, 77.8% for T3 and 71.4% for T4). Moreover, the methylation level of DMRTA2 can also distinguish BC from other interfering urinary cancer and benign BC.…”
Section: Methylationmentioning
confidence: 99%
“…Notably, however, Deng et al developed a single methylation biomarker model [ 74 ]. They used multiple validation steps involving TCGA data, BCa cell lines, and BCa patient cohorts to find the hypermethylation marker that provided the best diagnostic result; in the end, DMRTA2 achieved 82.9% SN and 92.5% SP, with an AUC of 0.93 in the diagnosis of BCa.…”
Section: Diagnostic Utility Of Biomarkers Assessed By Liquid Biopsymentioning
confidence: 99%